2008
DOI: 10.1038/bjp.2008.240
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and reliable proarrhythmia in vivo animal models for predicting drug‐induced torsades de pointes in patients with remodelled hearts

Abstract: As an increasing number of non-cardiac drugs have been reported to cause QT interval prolongation and torsades de pointes (TdP), we extensively studied the utility of atrioventricular (AV) block animals as a model to predict their torsadogenic action in human. The present review highlights such in vivo proarrhythmia models. In the case of the canine model, test substances were administered p.o. at conscious state 44 weeks after the induction of AV block, with subsequent Holter ECG monitoring to evaluate drug e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
114
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(121 citation statements)
references
References 86 publications
6
114
1
Order By: Relevance
“…Next, we examined the cardiovascular effects of dl-sotalol on the halothane-anesthetized microminipigs. We compared these results with those obtained by the halothane-anesthetized canine model (Ishizaka et al, 2008), since the canine model has been demonstrated to be useful for predicting the drug-induced cardiohemodynamic and electrophysiological responses in humans (Sugiyama, 2008). We found that each cardiovascular response was directionally the same as that reported in dogs, although the extent of the changes was greater in microminipigs than in dogs under the same anesthetic condition (Ishizaka et al, 2008).…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…Next, we examined the cardiovascular effects of dl-sotalol on the halothane-anesthetized microminipigs. We compared these results with those obtained by the halothane-anesthetized canine model (Ishizaka et al, 2008), since the canine model has been demonstrated to be useful for predicting the drug-induced cardiohemodynamic and electrophysiological responses in humans (Sugiyama, 2008). We found that each cardiovascular response was directionally the same as that reported in dogs, although the extent of the changes was greater in microminipigs than in dogs under the same anesthetic condition (Ishizaka et al, 2008).…”
Section: Discussionmentioning
confidence: 77%
“…Since net effect of β-adrenoceptor blocking activity of dlsotalol in microminipigs would be more potent than that in dogs as discussed above, dl-sotalol may more strongly suppress the constitutively operating inward Ca 2+ current in microminipigs than in dogs, which could counteract the consequence of I Kr and I Ks inhibition, resulting in the lack of change in the J-T peak c. These results may partly explain that torsade de pointes was not induced in the chronic atrioventricular block microminipigs following the administration of 10 mg/kg p.o. of dl-sotalol , although the lethal arrhythmia was observed with high reproducibility in the chronic atrioventricular block dogs (Sugiyama, 2008).…”
Section: Predictability Of Proarrhythmic Potential Of Dlsotalolmentioning
confidence: 90%
See 3 more Smart Citations